Pharmacotherapy of anxiety disorders in the 21st century: A call for novel approaches - Eric Bui; Franklin King; Andrew Melaragno (General Psychiatry)
While limited advances have occurred in the past 30 years in the pharmacological management of anxiety and stress-related disorders, novel molecular pathways both within and without the monoamine systems are currently under investigation and offer promising new avenues for more effective future treatments. Enhancing psychotherapy approaches with pharmacological compounds offers the potential to not only transform the standard of care of these conditions, but more broadly would introduce a paradigm shift in the way medications and their role in psychiatric care are conceptualised. Although further human trials and more translational research are sorely needed, continuing to pursue innovative mechanisms and treatments is hoped to yield substantial results in the coming decades and a departure from the reliance on chemical agents of the 20th century.